Integrating Design Thinking into Vocational Trainer Development A 5-Level Competency Framework for the AI and ESG ERA - Yeung, Shirley Mo-Ching; Yu, Kenneth Sau-Yin; Wong, Johnny Chung-Yee (International Journal of Independent Research Studies, 2026)
This paper presents a comprehensive framework for developing vocational trainers by integrating design thinking with the Hong Kong Qualifications. Framework (QF). It aims to bridge the gap between academic qualifications and practical vocational skills, explicitly addressing the emerging demands of artificial intelligence (AI) and environmental, social, and governance (ESG) competencies in the global training sector. The study employs a practice-informed research approach, synthesizing insights from the extensive professional expertise of the co-authors from the World Trainer Organization and applying the five-stage design thinking process. This methodology is used to develop and articulate a structured 5-Level Trainer. Course Framework (5LT), which is then mapped onto QF Levels 3–7 to ensure academic rigor and vocational relevance. The research identifies that a world-class trainer requires a synergistic combination of three core elements: 1) specific personal attributes, including adaptability and ethical mindset, 2) advanced curriculum design and delivery capabilities, and 3) external professional recognition through accredited certification. The 5LT framework provides a clear developmental pathway that systematically progresses from foundational training assistance to master-level strategic innovation. Vocational training institutions, corporate learning departments, and accreditation bodies can implement this framework to standardize trainer development, enhance training quality, and ensure alignment with industry needs and the Sustainable Development Goals. The framework offers a scalable model for cultivating trainers who can effectively respond to technological and social transformations. This paper offers a novel, integrated model that combines human-centered design thinking with a structured competency framework for vocational trainers. It provides both a theoretical contribution to the literature on professional education and a practical toolkit for organizations seeking to develop future- ready training talent.